Anatomophysiological modifications induced by solid agricultural waste (vermicompost) in lettuce seedlings (Lactuca sativa L.) - Argüello, Juan Alberto (2013)
Fil: Argüello, Juan Alberto. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Cátedra de Fisiología Vegetal; Argentina.